Measurements of Fitness and Competition in Commensal Escherichia coli and E. coli O157:H7 Strains - Durso, Lisa M. (American Society for Microbiology, 2004)
Although the main reservoirs for pathogenic Escherichia coli O157:H7 are cattle and the cattle environment, factors that affect its tenure in the bovine host and its survival outside humans and cattle have not been well studied. It is also not understood what physiological properties, if any, distinguish these pathogens from commensal counterparts that live as normal members of the human and bovine gastrointestinal tracts. To address these questions, individual and competitive fitness experiments, indirect antagonism assays, and antibiotic resistance and carbon utilization analyses were conducted using a strain set consisting of 122 commensal and pathogenic strains. The individual fitness experiments, under four different environments (rich medium, aerobic and anaerobic; rumen medium, anaerobic; and a minimal medium, aerobic) revealed no differences in growth rates between commensal E. coli and E. coli O157:H7 strains. Indirect antagonism assays revealed that E. coli O157:H7 strains more frequently produced inhibitory substances than commensal strains did, under the conditions tested, although both groups displayed moderate sensitivity. Only minor differences were noted in the antibiotic resistance patterns of the two groups. In contrast, several differences between commensal and O157:H7 groups were observed based on their carbon utilization profiles. Of 95 carbon sources tested, 27 were oxidized by commensal E. coli strains but not by the E. coli O157:H7 strains. Despite the observed physiological and biochemical differences between these two groups of E. coli strains, however, the O157:H7 strains did not appear to possess traits that would confer advantages in the bovine or extraintestinal environment.